Water‐Assisted Growth: Bifunctional Perovskite‐BiVO4 Tandem Devices for Uninterrupted Solar and Electrocatalytic Water Splitting Cycles (Adv. Funct. Mater. 15/2021). (8th April 2021) - Pornrungroj, Chanon; Andrei, Virgil; Rahaman, Motiar; Uswachoke, Chawit; Joyce, Hannah J.; Wright, Dominic S.; Reisner, Erwin
Abstract : Photoelectrocatalysis can directly store solar energy in chemical fuels like hydrogen, but its performance relies on external factors (such as light intensity and weather). In article number 2008182, Erwin Reisner and co‐workers report a hybrid perovskite‐BiVO4 device that can perform light‐driven water splitting during daytime and switch to water electrolysis at night, or when renewable electricity is more abundant.